The stomatal characteristics of monocots and dicots at different altitudes - Rusdi, Hasan; Tia, Setiawati; Mohamad , Nurzaman; Nopriyeni, Nopriyeni (Plant Science Today, 2025)
This study investigates the differences in stomatal characteristics between plants growing in lowland and highland altitudes, focusing on parameters such as stomatal type, distribution, number, density and index. A quantitative descriptive approach was employed, with sample collection conducted through purposive sampling. A total of 144 leaves were collected from 8 species, including both dicot and monocot, originating from low and high-altitude areas. The dicot species investigated were Capsicum annuum L., Mangifera indica L., Manilkara zapota (L.) P. Royen, and Psidium guajava L., while the monocot species included Cocos nucifera L., Colocasia esculenta (L.) Schott, Curcuma longa L., and Oryza sativa L. Stomatal number, density, and index were statistically analyzed using the t-test, whereas other parameters were assessed descriptively. The results revealed diverse stomatal types and distributions among the examined plant species. For instance, P. guajava exhibited paracytic stomata, C. annuum L. displayed anisocytic stomata, and C. esculenta had a distinct brachy-paracytic stomatal complex of, each plant manifests unique anatomical characteristics. The finding indicated that stomatal attributes, including number, density and index did not differ significantly between plants inhabiting lowland and highland environments within an altitude range of 550 m. This study highlights the influence of broader altitude variations and ecological factors influence stomatal features across diverse plant species.